Simultaneous MEG and EEG source imaging of electrophysiological activity in response to acute transcranial photobiomodulation - Pruitt, Tyrell; Davenport, Elizabeth M.; Proskovec, Amy L.; Maldjian, Joseph A.; Liu, Hanli (Frontiers in Neuroscience, 2024)
Transcranial photobiomodulation (tPBM) is a noninvasive neuromodulation technique that improves human cognition. The effects of tPBM of the right forehead on neurophysiological activity were previously investigated using EEG. Magnetoencephalography (MEG) records extracranial magnetic signals enabling a higher spatial resolution of brain source images. This study presents the first concurrent MEG and EEG measurements of post-tPBM effects across the entire human brain. MEG and EEG scans were concurrently acquired for 6 min before and after 8-min of tPBM delivered using a 1064-nm laser on the right forehead of 25 healthy participants. Group-level changes in both MEG and EEG power spectral density with respect to the baseline (pre-tPBM) were quantified and averaged within each frequency bands, respectively, in sensor space. Constrained modelling was used to generate MEG and EEG source images of 8-min 1064-nm right prefrontal tPBM, followed by cluster-based permutation analysis for family wise error correction (p<0.05). 8-min of tPBM demonstrated significant increases in both the alpha (8-12 Hz) and beta (13-30 Hz) frequency power across multiple cortical regions, as confirmed by both MEG and EEG source images. tPBM-induced oscillations in the beta frequency band were not only located near the prefrontal site but also in remote cerebral regions, including the frontal, parietal, and occipital regions, with a greater emphasis on the ipsilateral side. The EEG topographies observed in this study were consistent with those reported in the literature. This study provides MEG/EEG evidence of the electrophysiological effects of tPBM in local and distant cortical regions, supporting the potential utility in modulating neurological disease.